2013
DOI: 10.1371/journal.pone.0074602
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Serine Protease Inhibitor, SERPINE2, and the Urokinase Plasminogen Activator in Cumulus Expansion and Oocyte Maturation

Abstract: The serpin peptidase inhibitor, clade E, member 2 (SERPINE2) inhibits urokinase-type plasminogen activator (PLAU) and tissue-type plasminogen activator. Higher SERPINE2 expression levels were detected in cumulus cells of human immature oocytes than in those of mature oocytes. The objective of this study was to evaluate whether high SERPINE2 levels in cumulus cells are associated with oocyte immaturity. Using the mouse cumulus–oocyte complex as an experimental model, the effects of elimination and overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Since both the serine protease inhibitors and SERPINE1/2 prevent the conversion of plasminogen to plasmin, the present data argue for an important role of this serine protease in regulation of cumulus expansion in the pig. The inhibitory effect of SERPINE1/2 on HA retention observed in our study is in line with the results of a previous study in mice (Lu et al., ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Since both the serine protease inhibitors and SERPINE1/2 prevent the conversion of plasminogen to plasmin, the present data argue for an important role of this serine protease in regulation of cumulus expansion in the pig. The inhibitory effect of SERPINE1/2 on HA retention observed in our study is in line with the results of a previous study in mice (Lu et al., ).…”
Section: Discussionsupporting
confidence: 94%
“…In our previous study, we documented that FSH induced in porcine cumulus cells the upregulation of genes involved in blood coagulation and fibrinolysis, such as tissue‐type plasminogen activator ( PLAT ), urokinase‐type plasminogen activator receptor ( PLAUR ) and plasminogen activator inhibitor 1 ( SERPINE1 ; Blaha, Nemcova, Kepkova, Vodicka, & Prochazka, ). PLAT and PLAUR regulate the conversion of plasminogen into the active serine protease plasmin, whereas SERPINEs inhibit PLAT and PLAU activity and hence work as inhibitors of plasmin‐related proteolytic activity (Lu et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been reported that SERPINE2 was highly expressed in the endometrium during the secretory phase compared with the proliferative phase, indicating that it may participate in tissue remodeling during implantation in the placenta and uterus (31,32). A high SERPINE2 level was found in the inhibition of cumulus expansion and oocyte maturation (33). Interestingly, chromogranin A could promote secretory granule biogenesis in endocrine cells through up-regulation of the expression of SERPINE2 via a cAMP-protein kinase A-Sp1 pathway to replenish released granules (34).…”
Section: Discussionmentioning
confidence: 99%
“…Limited efforts have been taken to make use of clinically discarded CCs. In one direction, gene expression patterns in CCs were used to predict the oocyte quality and consequently the developmental competency of the derivative embryos [30]. …”
Section: Discussionmentioning
confidence: 99%